The Impact of Strategic Planning in Higher Education Institutions on the Needs of the Business Market in the Sultanate of Oman - Abdullah Said Obaid ALSHAAIBI; Khairunneezam MOHD NOOR (Rimar Academy, 2024)
Volume: 5 Issue: 3